True crime and women: new perspectives - Pâquet, Lili (True crime and women, 2025)
True crime is a genre that has provoked divisive responses of enjoyment and censure across its history in the English language. Because of the many, varied ways that it has been consumed and judged, true crime has been defined in often contradictory ways. The genre is consumed by a largely female audience. This chapter offers a new definition of true crime, focusing on its appeal to women. To achieve this aim, the chapter introduces the subsequent edited collection with contextual information about the genre of true crime and its significance to women as creators, writers, and researchers, and as real people represented in texts as either victims, survivors, or perpetrators. The chapter provides a brief history of true crime through its various media, such as specialist magazines, mass-produced paperbacks, documentaries, radio broadcasts, and podcasts. It concludes with a new definition of true crime and identifies potential future directions for research.